2018
DOI: 10.1534/genetics.118.301298
|View full text |Cite
|
Sign up to set email alerts
|

Can Deep Learning Improve Genomic Prediction of Complex Human Traits?

Abstract: The genetic analysis of complex traits does not escape the current excitement around artificial intelligence, including a renewed interest in "deep learning" (DL) techniques such as Multilayer Perceptrons (MLPs) and Convolutional Neural Networks (CNNs). However, the performance of DL for genomic prediction of complex human traits has not been comprehensively tested. To provide an evaluation of MLPs and CNNs, we used data from distantly related white Caucasian individuals (n 100k individuals, m 500k SNPs, and k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
229
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(268 citation statements)
references
References 35 publications
(33 reference statements)
23
229
3
Order By: Relevance
“…SNPs in the context of this study; the last layer outputs the final result of the model and the layer(s) in between are called hidden layer(s). A function node in hidden and output layers typically transforms the inputs from the previous layer with a weighted linear sum followed by an activation function 23 . For example, f 1 in Figure 2 can be represented as:…”
Section: Polygenic Scoring Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…SNPs in the context of this study; the last layer outputs the final result of the model and the layer(s) in between are called hidden layer(s). A function node in hidden and output layers typically transforms the inputs from the previous layer with a weighted linear sum followed by an activation function 23 . For example, f 1 in Figure 2 can be represented as:…”
Section: Polygenic Scoring Methodsmentioning
confidence: 99%
“…As this work is, to our knowledge, the first attempt to employ MLPs and CNNs for genomic prediction of blood cell traits, there was no prior information that could be used for the design of network architecture for this task. Therefore, similar to the previous work 23 , we used a genetic algorithm to search for the optimal MLP and CNN architectures as well as other hyperparameters, e.g. the number of layers, the number of neurons at each layer, activation functions, optimizers, dropouts, etc., on the train set, in which 10% of the samples were used as a validation set.…”
Section: Measurement and Hyperparameter Tuningmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we observe some marked improvements of Promoter-CNN + ALS-Net over logistic regression. An explanation might be that Bellot et al (2018) use a (substantially) simpler (nondeep) network architecture and make a pre-selection of genetic features based on linear models, and hence overlook non-additive interactions already in the pre-selection step.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have considered using deep learning for genotype-phenotype association studies. Most approaches first reduced the number of variants included in the model either by selecting variants that were known to be associated with disease (Uppu and Krishna, 2017;Hess et al, 2017), or by preselecting those variants that showed a sufficiently strong correlation with phenotype in a regular GWAS (Montañez et al, 2018b;Bellot et al, 2018). Two studies combine the latter strategy with the use of autoencoders for further dimensionality reduction (Montañez et al, 2018a;Fergus et al, 2018).…”
Section: Introductionmentioning
confidence: 99%